2002
DOI: 10.1177/10634266020100020101
|View full text |Cite
|
Sign up to set email alerts
|

Those Who Do Not Return

Abstract: In this article we examine the facility-to-community transition experiences of formerly incarcerated youth in the sample who remained in the community for 1 year following release from the juvenile correctional system. Specifically, we studied the relationship of selected predictor variables to engagement status (a transition outcome based on working, going to school, or both activities) at two points in time after the participants exited the juvenile correctional system: 6 months post-exit (Time 1) and 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…For example, in their study of over 500 formerly incarcerated youth in Oregon, Bullis and Yovanoff (2002) found that only 30% were enrolled in school or substantially employed at 1 year post release. Additional research has discovered that returning youth offenders commonly struggle to find safe and stable housing after leaving the correctional system, and a high proportion of offenders (estimates lie between 40% and 60%) contend with mental health challenges and/or substance abuse disorders (Altschuler and Brash 2004; Teplin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in their study of over 500 formerly incarcerated youth in Oregon, Bullis and Yovanoff (2002) found that only 30% were enrolled in school or substantially employed at 1 year post release. Additional research has discovered that returning youth offenders commonly struggle to find safe and stable housing after leaving the correctional system, and a high proportion of offenders (estimates lie between 40% and 60%) contend with mental health challenges and/or substance abuse disorders (Altschuler and Brash 2004; Teplin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from longitudinal studies have shown that juvenile offenders are likely to experience persistent social problems such as unemployment, low educational attainment, homelessness, and recidivism into the juvenile and adult penal systems (Bullis and Yovanoff 2002; Snyder and Sickmund 2006). These negative outcomes stem in part from exposure to childhood risks that are known to contribute to negative life outcomes, such as child abuse and neighborhood disorganization.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this possibly resulted in limited employment opportunities. According to previous research, the experience of imprisonment complicates graduation or finding employment (Bullis & Yovanoff, 2002;Van der Geest et al, 2016). Another explanation might be possible stigmatization during the job application process as a result of past convictions or imprisonment (Decker et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Adolescentlimited offending is common and generally considered to be a normative response to the social context of an adolescent, whereas life course persistent offending is more rare and often related to experienced family adversities, inadequate parenting, neurocognitive problems, and temperament and behavior problems (Moffitt & Caspi, 2001). According to previous studies, youth who commit frequent and serious crimes in adolescence tend to be less successful later in life than non-offending youth: They are frequently engaged in multiple types of crimes during young adulthood (Piquero et al, 2012) and experience difficulty in finishing school and finding employment (Bullis & Yovanoff, 2002;Van der Geest et al, 2016). In turn, this relates negatively to quality of life (QoL) in young adulthood (Lanctôt et al, 2007).…”
mentioning
confidence: 99%
“…There is some evidence that use of formal neighborhood resources may positively influence the transition to school and work and can potentially deter recidivism. Bullis & Yovanoff’s (2002) longitudinal study of over 500 released youth in Oregon found that those who engaged mental health services were 4.8 times as likely to be engaged in work or school at one year post release. In a separate analysis, they found that these “engaged youth’ were at least twice as likely as those who were not engaged to avoid repeat contact with the criminal justice system (Bullis, Yovanoff, Mueller, & Havel, 2002).…”
Section: Theory and Research Supporting A Neighborhood-based Reentry mentioning
confidence: 99%